2014
DOI: 10.1021/am503914q
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic and Dye-Sensitized Solar Cell Performances of {010}-Faceted and [111]-Faceted Anatase TiO2 Nanocrystals Synthesized from Tetratitanate Nanoribbons

Abstract: The morphology and exposed facet of the anatase-type TiO2 are very important to improve the photocatalytic activity and photovoltaic performance in dye-sensitized solar cells. In this work, we report the synthesis and the photocatalytic and dye-sensitized solar cell performances of anatase-type TiO2 single nanocrystals with exposed {010}- and [111]-facets and with various morphologies by using exfoliated tetratitanate nanoribbons as precursors. The precursor nanoribbons were prepared from the exfoliation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 76 publications
4
58
0
Order By: Relevance
“…Figures (a), (b), (e), and (h) show the FESEM images of the mixed phase of anatase TiO 2 and layered titanate, the nanospindles and nanoribbon can be indexed to the anatase TiO 2 and tetratitanate phase, respectively. In view of the growth direction of tetratitanate along the b ‐axis of the crystal, therefore, the growth direction of the nanospindles along the [001] direction, which is perpendicular to the [010]‐axis of the tetratitanate nanoribbon. The result means that the anatase TiO 2 nanospindles are formed by split the exfoliated [Ti 4 O 9 ] −2 nanoribbon along the [001] direction, and accompanied by a dissolution process.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Figures (a), (b), (e), and (h) show the FESEM images of the mixed phase of anatase TiO 2 and layered titanate, the nanospindles and nanoribbon can be indexed to the anatase TiO 2 and tetratitanate phase, respectively. In view of the growth direction of tetratitanate along the b ‐axis of the crystal, therefore, the growth direction of the nanospindles along the [001] direction, which is perpendicular to the [010]‐axis of the tetratitanate nanoribbon. The result means that the anatase TiO 2 nanospindles are formed by split the exfoliated [Ti 4 O 9 ] −2 nanoribbon along the [001] direction, and accompanied by a dissolution process.…”
Section: Resultssupporting
confidence: 91%
“…It can be observed that only a set of lattices is present and it is parallel to the edge of the rutile rectangular parallelepiped with an interfringe spacing of 0.325 nm (corresponding to rutile TiO 2 (110) planes), indicating preferential growth direction of the rutile rectangular parallelepiped along the [001] direction . In view of the growth direction of H 2 Ti 4 O 9 along the [010]‐axis of the crystal, we think that the rutile TiO 2 nanocrystals is formed by dissolved the exfoliated [Ti 4 O 9 ] −2 nanoribbon along the [001] direction, accompanied by the recrystallization of the dissolved structural units. Therefore, it can be concluded that the quadrangular prismatic rutile TiO 2 nanocrystals is bounded by {110} facets on the four sides and {001} facets on both the top and bottom.…”
Section: Resultssupporting
confidence: 67%
“…reported that square‐shaped anatase TiO 2 crystals with dominantly exposed [111]‐facets were prepared by a solid‐state method, which exhibited obvious higher photocatalytic activity toward efficient H 2 evolution . We also synthesized high‐quality anatase TiO 2 nanorods with exposed [111]‐facets for the first time by using the [Ti 4 O 9 ] 2− nanoribbons or [TiO 3 ] 2− nanosheets as the processor under hydrothermal conditions ,. Using the oleylamine as the morphology controlling agent and HF as the stabilizing agent, Amoli et al.…”
Section: Introductionmentioning
confidence: 99%
“…The rutile is a thermodynamically stable phase, whereas anatase and brookite are metastable phases under ambient conditions . The anatase and brookite are relatively stable in low acidic and alkaline solutions, while rutile in relatively high acidic solution under hydrothermal conditions …”
Section: Introductionmentioning
confidence: 99%
“…The topochemical process using a layered compound as the precursor is an effective method for the synthesis of the metastable phases. The layered titanate nanosheets have been used as the precursor for the synthesis of anatase nanocrystals with a specific facet on the nanocrystal surface ,. Ban et al .…”
Section: Introductionmentioning
confidence: 99%